O CINEMA COMO RECURSO DIDÁTICO-PEDAGÓGICO NO ENSINO JURÍDICO: QUEBRANDO PARADIGMAS - Pinho, Ana Carla de Oliveira Mello Costa (2013)
This issue aimed, as a general objective, to investigate the didactic-pedagogical model which has been present in the Brazilian legal education, highlighting the need for searching the integral formation of the future legal and judicial operators, according to the CNE/CES n° 09/04 Resolution. Specifically, it aimed to investigate how the use of movies can be understood as a resource in order to open possibilities for the interaction among the legal areas and other areas, including art and esthetics focusing the formation of the law student regarding his/her effectiveness in thinking, to broad his/her world vision and offer conditions for better critical thinking. The ways gone through in this research have included a theoretical study about the history and the problems of the legal education in Brazil, discussing the pedagogical characteristics related to it as well the innovations brought by MEC regarding the curricula and pedagogy adjustment in order to reach the humanistic education, according to the academic reality of our dynamic and globalized society. The research provides a problematization in terms of how films, considered as an instructional tool, can be used as inter and transdisciplinar method in law school. It has also been produced a field research, taking a qualitative approach through questionnaire, which intended to listen to the students opinion about an experience in International Law where, regularly, cinema has been used as a strategy to contextualize the issues. The research has showed that only few professors have been using this dialogical tool in their classes.